KAJIAN ETNOTAKSONOMI Pandanus conoideus Lamarck UNTUK MENJEMBATANI PENGETAHUAN LOKAL DAN ILMIAH - Walujo, Eko B; Keim, Ary P; S, Maria Justina (Research Center for Biology-Indonesian Institute of Sciences, 2007)
Red pandan (Pandanus conoideus Lamarck) is an important plant for the people of the Arfak Mountain in the Province of Papua Barat (West Papua), Indonesia that include the tribes of Meyah, Sougb and Hatam. In total there are 10 morphological variations found, each with a local (vernacular) name.The local nomenclature used by the three tribes is in correspondence with the formal botanical nomenclature, but not identical. The result of the ethnotaxonomical study shows that the basic name equals to species name, while attribute refers to infraspecific classification.Attribute is suggested to be addressed to the category of variety in the formal (botanical) taxonomy rather than to subspecies.Ethnotaxonomy is proven to be a good alternative solution for the problems faced in the formal taxonomy.